Structure and composition of linear TiOx nanostructures on SrTiO3(001) - Marshall, M; Becerra-Toledo, A; Payne, D; Egdell, R; Marks, L; Castell, M (2012)
High-resolution x-ray photoelectron spectroscopy (XPS) was performed on the surface of 0.7 at.% Nb-doped SrTiO 3(001) decorated with self-assembled linear nanostructures termed dilines, trilines, and tetralines. All three nanoline types share a common side-row feature, while the triline is shown to contain Ti in the 2+ oxidation state as a structural component of the linear backbone. Atomic-resolution scanning tunneling microscopy images and models developed using density functional theory are used to relate the structures to the spectroscopic data, showing that the nanolines consist of a three-layer hill and valley-type structure. Valence band XPS reveals the presence of a well-defined mid-band-gap state at approximately 1 eV, which emerges as a result of nanoline formation. © 2012 American Physical Society.